The billion dollar BET : - Pulley, Brett (John Wiley, 2004)
Those interested in business are not the only ones who will welcome The Billion Dollar BET (Wiley; 24.95). Robert Johnson’s rise from humble beginnings in Hickory, Miss and Freeport, Ill to bone a fide American billionaire is packed with all the elements of great stories. In addition to a healthy dose of drive and determination, there is a large helping of alleged backstabbing, extramarital affairs, corporate meltdowns and showdowns.